The bioaccumulation testing strategy for nanomaterials: correlations with particle properties and a meta-analysis of in vitro fish alternatives to in vivo fish tests. Issue 2 (7th January 2022) - Handy, R. D.; Clark, N. J.; Boyle, D.; Vassallo, J.; Green, C.; Nasser, F.; Botha, T. L.; Wepener, V.; van den Brink, N. W.; Svendsen, C.
Abstract : This meta-analysis identifies linkages between the tiers in the bioaccumulation testing strategy. Abstract : For manufactured nanomaterials (MNs), given the breadth of forms produced, it is not ethical or practical to test all materials using vertebrates. This study aimed to show how alternative methods could predict the in vivo bioaccumulation potential of MNs in fish. This included exploring the physico-chemical properties of MNs as predictors of bioaccumulation, using the ex vivo gut sac technique to measure total metal uptake, and an in chemico digestibility assay to simulate the bioaccessible metal in the gut lumen of fish. An apparent plateau in net metal accumulation by rainbow trout was evident from data on dietary exposures to CuO nanoparticles (NPs), Ag NPs or Ag2 S NPs in vivo . From the metal concentrations in the tissues compared to the diet, it was possible to derive nano biomagnification factors ( n BMFs). The n BMF for the liver showed the best correlations with the physico-chemical parameters, with a significant correlation to the particle dissolution rate (Spearman's correlation, p < 0.01). Moreover, there was a significant relationship between the total metal released in the stomach compartment of the digestibility assay and the total metal concentration in the liver of trout in vivo (Pearson's correlation coefficient, p = 0.02), suggesting the in chemico digestibility assay can predict bioaccumulation potential. The ex vivo gut sac technique also gave good correlations to in vivo results, with r 2 values between 0.8–0.9. In conclusion, the meta-analyses supports the development of an integrated and tiered approach to bioaccumulation testing that considers the 3Rs (replacement, reduction, refinement) and minimises the use of the fish bioaccumulation test (OECD TG 305), for nanomaterials.